Central manifolds of quasilinear parabolic equations - Belan, E. P.; Lykova, O. B. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We investigate central manifolds of quasilinear parabolic equations of arbitrary order in an unbounded domain. We suggest an algorithm for the construction of an approximate central manifold in the form of asymptotically convergent power series. We describe the application of the results obtained in the theory of stability.